Gestión administrativa del desarrollo de indicadores de venta cruzada en el área comercial del Banco Pichincha, agencia La Maná, año 2014 - Chevez Barba, Mercedes Fernanda (2015)
Banco Pichincha is a financial institution that contributes to the development of Ecuador, supporting their financial needs individuals, institutions and companies. Market leader in its image, participation, quality of products and services focused their efforts towards customers, anticipating their needs, developing staff and providing sustainable profitability and actions. This work will help in the implementation of a new service for customers of the commercial area in Pichincha bank agency in La Mana, the bank will offer the experience of its highly qualified personnel with innovative, efficient and creative capacity, with high professional career in the implementation of new services in the commercial bank to advise clients and process the information that allows the manager easily deploy the new service successfully. In the development of qualitative and quantitative research methodologies .The first group comprises techniques such as field observation, data collection, and interviews that were conducted were implemented Ing. Manuel Eduardo CerdaMolestina bank manager Pichincha La Manna agency in second group comprises the methodology through surveys of 384 customers of the financial institution employees. The implementation of strategies for cross-selling means to detect the needs of customers and achieve a new complementary offering banking product, the customer is willing to buy and the adviser must ensure that not later regret your purchase, therefore advisers the bank will be able to generate cross-selling opportunities to achieve more sales, which among other things allows customer loyalty. Negotiations are vital in commercial bank activities that allow them to obtain good economic benefits through the placement of banking products and services. The importance of cross-selling is determining which product will be offered to customers in the commercial area of La ManaBanco Pichincha agency and prior to an analysis of customer credit history.